2011
DOI: 10.1155/2011/523520
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-αAgonist Fenofibrate Upregulates Tetrahydrobiopterin Level through Increasing the Expression of Guanosine 5′-Triphosphate Cyclohydrolase-I in Human Umbilical Vein Endothelial Cells

Abstract: Tetrahydrobiopterin (BH4) is an essential cofactor for endothelial nitric oxide (NO) synthase. Guanosine 5′-triphosphate cyclohydrolase-I (GTPCH-I) is a key limiting enzyme for BH4 synthesis. In the present in vitro study, we investigated whether peroxisome proliferator-activated receptor α (PPAR-α) agonist fenofibrate could recouple eNOS by reversing low-expression of intracellular BH4 in endothelial cells and discussed the potential mechanisms. After human umbilical vein endothelial cells (HUVECs) were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
3
23
0
Order By: Relevance
“…21 In the present study, we report for the first time that endothelial cell eNOS protein is increased in humans with fenofibrate treatment. This finding is consistent with previous data showing that fenofibrate increases eNOS protein expression in cultured endothelial cells 8, 22 and the aorta of rodents. 9 In contrast, eNOS protein expression was reported not to change and NO was reported not contribute to the improvements in dilation in response to acetylcholinein the small mesenteric arteries of old rats with fenofibrate treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…21 In the present study, we report for the first time that endothelial cell eNOS protein is increased in humans with fenofibrate treatment. This finding is consistent with previous data showing that fenofibrate increases eNOS protein expression in cultured endothelial cells 8, 22 and the aorta of rodents. 9 In contrast, eNOS protein expression was reported not to change and NO was reported not contribute to the improvements in dilation in response to acetylcholinein the small mesenteric arteries of old rats with fenofibrate treatment.…”
Section: Discussionsupporting
confidence: 93%
“…6 It is possible that fenofibrate may influence eNOS and the NO contribution to acetylcholine-induced dilation of small resistance arteries differently than in conduit arteries of humans in response to flow (present study), or in aorta or cell culture. 8, 22 We were unable to measure the NO contribution to dilation using the brachial FMD model, and thus cannot determine if the increased eNOS expression with fenofibrate had functional benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that metformin improved endothelial function by suppressing 26s proteasome-mediated GTPCH1 degradation to increase the level of BH4 (36). Furthermore, we reported previously that PPAR␣ agonist fenofibrate upregulated BH4 level by increasing the expression of GTPCH1 in HUVECs (26). Our results suggested that exendin-4 increased the level of GTPCH1 in a dose-and timedependent manner and thus might lead to improvement of the …”
Section: E954supporting
confidence: 64%
“…The umbilical cord samples were collected and washed three times with phosphate-buffered saline (PBS). Endothelial cells were isolated by collagenase digestion and cultured in Medium 199 (Hyclone, Logan, UT) supplemented with 10% fetal bovine serum (FBS), as described previously (26). The cells of five to six passages were used in all experiments, which were examined to ensure specific characteristics of endothelial cells by cytochemical staining.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…•2 content (Okayasu et al, 2008;Potenza et al, 2009;Antoniades et al, 2011;Liu et al, 2011a). Time-and concentration-dependent effects are also apparent after exposure of rats to environmentally relevant low-tomoderate As III levels in drinking water [20 mg/l; with 10 mg/l deemed as the safe level by the World Health Organization (http://www.who.int/water_sanitation_health/publications/2011/ dwq_guidelines/en/)], where acetylcholine-induced aortic relaxation is maintained after 2 months but reduced after 7 months' exposure (Cifuentes et al, 2009).…”
Section: Implies That Omentioning
confidence: 99%